From Fenye to Latitude and Longitude: The Adjustment and Renewal of the Positioning System in Chinese Local Gazetteers during Qing Dynasty - Zhang Jiajing (HoST, 2024)
Influenced by a cosmological view of the interconnectedness between heaven and humankind, ancient Chinese astrologers developed the fenye (分野, “field allocation”) system. This theory envisioned correspondence between heaven and earth and was a prevalent regional positioning system in ancient China. However, during the Qianlong era (1736-1796), fenye theory faced skepticism and rejection from official quarters, leading to a significant crisis for this traditional positioning system. With the eastward spread of Western learning, modern European astronomical and geographical knowledge were introduced into China, and Chinese intellectuals began to favor the Western system of latitude and longitude for geographical positioning. In the late Qing period, the gradual popularization of the spherical Earth concept and the latitude and longitude system laid the theoretical foundation for establishing of this system. The public dissemination of latitude and longitude data measured by the imperial astronomical and calendrical institutions, along with mathematicians’ calculations based on historical data and the supplementary measurements conducted by local governments, provided data support for the system’s establishment. By the end of the Qing dynasty, as the knowledge structures and worldviews of Chinese intellectuals transformed, the traditional celestial-terrestrial correspondence in Chinese local gazetteers was phased out, giving way to the latitude and longitude system.